Identifikasi Faktor Utama Penyebab Voluntary Turnover di PT X - Bella Eka Fianty; Prayonne Adi (Jurnal Titra, 2020)
One of the challenges experienced by many organizations today is the high rate of employee turnover. This is no exception for PT X. High employee turnover rates, especially those that occur voluntarily can have a negative impact on the organization, both related to tangible and intangible costs. The level of employee turnover that occurs voluntarily at PT X in 2017-2019 has an average of 5.45%-5.77% with an increasing trend from year to year. Y Department is a function of Human Resources that runs job desc under the pillars of employee engagement. Through Y Department, the company expects to reduce voluntary turnover. The voluntary turnover effort is designed based on the identification of the main factors causing voluntary turnover. Identification is done through the Spearman 's Rho and Kendall’s tau correlation test, then proceed with ordinal regression modeling of employee resignation reasoning data and employee assessment of the company. Confirmation of the needs of some active employees is also taken into consideration.